Pharmacological management of acute respiratory tract infections in emergency department of tertiary care center - Shrestha, Ruchi; Shrestha, Roshana; Shrestha, Sony Shakya; Manandhar, Jyoti Tara (Journal of Chitwan Medical College, 2021)
Background: Acute respiratory tract infection has been recognized as the major cause of morbidity and ranks among the most frequent causes of mortality among the elderly and very young children. This study aimed to assess the pharmacological management of acute respiratory tract infections among patients visiting Emergency Department in Dhulikhel Hospital, Kathmandu University Hospital. Methods: A descriptive, cross sectional study was conducted from August 2019 to January 2020 in patients attending Emergency Department of Dhulikhel Hospital. One hundred and sixty five patients with symptoms of acute respiratory tract infections who visited the same department were included in the study. Entry and analysis of collected data was done in Statistical Package for the Social Sciences 20. Descriptive tests were used, and results were expressed as mean, frequency and percentage. Results: Among 165 patients who visited Emergency department with symptoms of acute respiratory tract infections, majority 137 (83%) had symptoms of shortness of breath, followed by cough 110 (66.7%). Thirty (18.2%) cases were triaged into high acuity (red) zone. Acute exacerbation of chronic obstructive pulmonary disease 118 (71.5%), followed by pneumonia 16 (9.7%) were the most common diagnosis. Intravenous hydrocortisone was the most commonly used pharmacotherapy in 125 (75.8%) patients. Oxygen was most commonly used supportive therapy in 137 (83%) cases. Regarding the outcome, 75 (45.5%) were admitted to wards and 64 (38.8%) were discharged. Conclusions: Most of the acute respiratory tract infections were managed by using intravenous corticosteroid, antibiotics and nebulized bronchodilators.